Pengaruh Lingkungan Kerja dan Semangat Kerja Terhadap Kinerja Karyawan Pada PT. Nusantara Abadi Kreasi - Surya Asih (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
The purpose of this study was to determine whether a work environment and working spirit together influence the performance of employee at PT Nusantara Abadi Kreasi. Data collection techniques in this study was a questionnaire (Questionnaire), study of documents and interviews (Inteview). While the data analysis techniques used are validity, reliability test, the classical assumption test, multiple linear regression, F test and t test. Results of this study demonstrate that the variable working environment and working spirit partially significant effect on labor productivity at PT Nusantara Abadi Kreasi. Based on the results of the F test can be proved that the work environment and working spirit positive and significant impact on performance of employees at PT Nusantara Abadi Kreasi.